2022
DOI: 10.1029/2020jc017099
|View full text |Cite
|
Sign up to set email alerts
|

Submesoscale Coherent Vortices in the South Atlantic Ocean: A Pathway for Energy Dissipation

Abstract: Mesoscale eddies propagate westward across the South Atlantic basin. As they reach the westernmost part of the basin, at approximately 20°S, they interact with a quasi‐zonal seamount chain, the Vitória‐Trindade Ridge (VTR). The interactions with the local topography lead to submesoscales instabilities, which ignite the formation of submesoscale coherent vortices (SCVs) such as those described in the present study for the first time in the VTR region. Here, using high‐resolution hydrographic and microstructure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 60 publications
3
11
0
Order By: Relevance
“…Submesoscale motions can trigger the formation of mesoscale meanders, but the opposite is also true. The interaction of mesoscale meanders with topography can ignite symmetric and inertial instabilities (Napolitano et al, 2021a), and generate Submesoscale Coherent Vortices (SCVs) (Lazaneo et al, 2022). Such processes can enhance the vertical exchange of tracers and lead to energy dissipation (Gula et al, 2016b;Lazaneo et al, 2022).…”
Section: 1mentioning
confidence: 99%
See 3 more Smart Citations
“…Submesoscale motions can trigger the formation of mesoscale meanders, but the opposite is also true. The interaction of mesoscale meanders with topography can ignite symmetric and inertial instabilities (Napolitano et al, 2021a), and generate Submesoscale Coherent Vortices (SCVs) (Lazaneo et al, 2022). Such processes can enhance the vertical exchange of tracers and lead to energy dissipation (Gula et al, 2016b;Lazaneo et al, 2022).…”
Section: 1mentioning
confidence: 99%
“…In the last sections, we have shown that during this process, the shear between the cyclones and the topography increases anticyclonic vorticity and generates downscale KE uxes. In this section, we aim to answer if this process is associated with the development of inertial/symmetric instabilities and, subsequently, with the generation of anticyclonic SCVs (e.g., Molemaker et al, 2015;Morvan et al, 2019;Napolitano et al, 2021b;Lazaneo et al, 2022).…”
Section: Submesoscale Anticyclones Generationmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the processes responsible for enhancing the submesoscale dynamics are the interaction of local currents with the topography. Submesoscale studies about ow-topography interaction are recent (Ruan et al, 2017;Garabato et al, 2019;Napolitano et al, 2021;Lazaneo et al, 2022), as well as studies that investigate the dynamics of canyons through high resolution numerical modeling (Vic et al, 2018;Lahaye et al, 2019). The numerical models reveal that the large scale currents interacting with steep slopes, seamounts and ridges allow the formation of submesoscale currents (Gula et al, 2016b;Srinivasan et al, 2019;Vic et al, 2018) that create high rates of local kinetic energy dissipation (Gula et al, 2016b).…”
Section: Evaluation Of the Submesoscale Dynamicsmentioning
confidence: 99%